If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + x = -3x Solving 7 + x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7 + x + 3x = -3x + 3x Combine like terms: x + 3x = 4x 7 + 4x = -3x + 3x Combine like terms: -3x + 3x = 0 7 + 4x = 0 Add '-7' to each side of the equation. 7 + -7 + 4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 0 + -7 4x = 0 + -7 Combine like terms: 0 + -7 = -7 4x = -7 Divide each side by '4'. x = -1.75 Simplifying x = -1.75
| (x-4)=3x+4 | | 5/10=b/2 | | 4a-135=a/4 | | -6+4(-5+4n)=11+n | | 2w-3w=8w | | 1/4y=7/8 | | 12x+18=11x-7 | | 17/18x73 | | 5x+6-11=4x+3 | | 4/3(3.14)(9)E3 | | -6x-4(-6x-3)=257 | | 260-2/3 | | 4x-1=120 | | 6x+4-2x=16 | | -4(5-w)-(4w-8)=-12 | | -4(5-6)-(4w-8)=-12 | | -8+4v=12 | | 4/3(3.14)(3)E3 | | 8(x-2)=4y | | 4x+20=7x-25 | | -2(p-2)=-2(1-2p) | | -14-z/9=-12 | | 2(10+x)=90 | | 31=6+12+c | | 10x+1-2x=3+8x-10 | | -11=-5(3k+8)+8(-5-k) | | 4(2x-3)=x+9 | | -6(-6n+7)-7=-157 | | 12x-1=-7 | | 3-4(x-3)=3(x-6)-7x | | -21w+5+4w-1= | | 6(-4-x)=-18x |